Analisis Bioekonomi (Maximum Sustainable Yield dan Maximum Economic Yield) Multi Spesies Perikanan Laut Di PPI Kota Dumai Provinsi Riau - Hazmi Arief (Fakultas Perikanan dan Kelautan, Universitas Riau, 2016)
This research was conducted on to April to July 2016 in the city of Dumai in Riau province. Its was aimed to analyze the potential sustainability of the bioeconomy and forms of business management of marine fisheries in PPI Kota Dumai terms of Biological and Economic Aspects. The method used by survey methods, respondents were fishermen in PPI the city of Dumai. Based on the research linkage with the fishing effort CPUE (Cath Per Unit Effort) during the period 2000-2015 amounted to 0,003601 ton/trip. The highest value in 2015 amounted to 0,0047 ton/trip, meaning the catch is high but lower fishing effort, the lowest value occurred in 2011, namely 0.00199 indicate that the fishing effort of the catch was low but relatively high fishing effort.